Matriz para análise do uso de tecnologias recentes que potencializam os benefícios pedagógicos nos jogos de empresas - Alves, Juliano Barbosa (2010)
The use of business games as a tool to support education throughout the years has helped reduce the distance between the training courses given by the board and the expectations of the market. However, all this changing context and communication revolution creates the need for review of technical and conceptual games status is in keeping with new technological trends. This study aimed to provide a method of procedure for considering the use of recent technologies that leverage the pedagogical benefits already identified in the games business by developing a matrix of relationships that provide the benefits offered by educational games company, the dimensions key generators and the potentiating technologies that most affect these characteristics. For this, we performed a literature review in order to characterize the games business, the pedagogical benefits, the key dimensions and the latest technologies currently used for the development of business games. As a way to examine the consistency of the relationship matrix Games / Technology, surveyed are examples of successful application of the latest technology. Finally, a search was conducted through a quantitative approach to multiple cases to show the relevance level of each criterion identified in the matrix of relationships from the perspective of participants in business games. The results showed that the matrix is effective and offers references for analysis of alternatives and thinking processes of technological development and / or academic use of business games.